HEALING WORDS WITH MEANING: THE IMPACT OF EXISTENTIAL–HUMANISTIC GROUP COUNSELING ON VERBAL BULLYING SURVIVORS - Wahyudi; Nasruliyah Hikmatul Maghfiroh; Bhennita Sukmawati (EDUCATIONE, 2026)
This study aims to examine the effectiveness of the existential–humanistic approach in supporting the psychological recovery of verbal bullying victims in Islamic boarding schools. Verbal bullying can cause detrimental psychological impacts, such as decreased self-confidence, heightened anxiety, difficulty concentrating, declining academic performance, loss of interest in previous activities, and a reduction in previously positive social relationships, all of which hinder the emotional and academic development of students. Therefore, an intervention is needed to help victims of verbal bullying. The general objective of this study is to determine the extent to which group counseling using the existential–humanistic approach can improve the psychological condition of student victims of verbal bullying. The specific objectives are to measure changes in anxiety levels, concentration difficulties, academic performance, interest in activities, social relationships, and self-esteem after participating in group counseling sessions. This study employs a One Group Pre-Test Post-Test design, in which respondents are assessed before and after the group counseling intervention. Data will be collected using questionnaires measuring anxiety, depression, and self-esteem, and will then be analyzed to determine significant differences. The expected outcome of this study is to prove the effectiveness of group counseling with the existential–humanistic technique in reducing psychological disturbances among student victims of verbal bullying. The findings are anticipated to provide practical contributions to the development of counseling programs in Islamic boarding schools to support students’ mental well-being.